Wide-field electromagnetic method for deep hot dry rock fracturing monitoring: penetrating thick low-resistivity overburden - Shiyin Gao; Shiyin Gao; Wubing Deng; Juncheng Wang; Juncheng Wang; Juncheng Wang; Juncheng Wang; Mingzuan Xu; Mingzuan Xu (Frontiers in Earth Science)
IntroductionHot dry rock (HDR) geothermal reservoirs are a vital renewable energy source, but their exploitation requires hydraulic fracturing (HF) to enhance permeability. However, traditional electromagnetic (EM) methods face significant limitations in monitoring deep HDR fracturing due to the shielding effect of thick low-resistivity overburden layers (>4,000 m, ρ < 80 Ωm). Overcoming this challenge is critical for optimizing HF operations and ensuring reservoir efficiency.MethodsWe propose the wide-field electromagnetic method (WFEM) as a novel solution for real-time HF monitoring in shielded environments. Through 3D numerical simulations and field applications in an Ordovician-Cambrian HDR reservoir (4,200–5,600 m depth), we evaluated WFEM’s sensitivity to resistivity changes induced by fracturing fluids. Key acquisition parameters were optimized via forward modeling, including transmitter-receiver distance (*r* = 15 km), current (I = 130 A), and electrode spacing (AB = 3,000 m, MN = 100 m).ResultsField data revealed distinct resistivity reduction zones (1,000→25 Ωm) spatially correlated with active fracturing wells, demonstrating WFEM’s ability to detect fluid-induced anomalies (Δρ up to 30%). The method successfully mapped fluid distribution patterns, validating its resolution in deep, shielded geological settings.DiscussionThis study provides the first evidence of WFEM’s efficacy in monitoring deep HDR fracturing, offering a cost-effective alternative to microseismic methods. The results highlight WFEM’s potential for real-time HF monitoring in environments where conventional EM techniques fail. Future work should focus on integrating WFEM with multi-physical data to further improve fracture network characterization.